DIPG-76. PNOC-003: PRECISION MEDICINE TRIAL FOR CHILDREN WITH DIFFUSES INTRINSIC PONTINE GLIOMA: PRELIMINARY EXPERIENCE WITH MULTI-AGENT PERSONALIZED THERAPY RECOMMENDATIONS. Issue 2 (22nd June 2018) - Kilburn, Lindsay; Kuhn, John; Nazemi, Kellie; Molinaro, Annette; Liang, Winnie; Banerjee, Anu; Hwang, Eugene; Crawford, John; Nicolaides, Theodore; Packer, Roger; Nazarian, Javad; Gupta, Nalin; et al.
Abstract: New therapies for children with diffuse intrinsic pontine glioma (DIPG) are greatly needed. Within a prospective multi-center feasibility trial, we evaluated whether genomic profiling (tumor and germline exome sequencing and tumor RNA) could be used to identify targetable events to inform a treatment recommendation from a multidisciplinary tumor board within 21 business days after biopsy recommending up to four FDA approved drugs to start following focal radiotherapy. Agents were prioritized that target DNA alterations and have available pediatric safety and dosing information. Agents were introduced in a sequential manner with close toxicity monitoring when there was limited experience for the combinations. Seventeen patients were enrolled. Fourteen of the 15 eligible patients had complete profiling and generation of a tumor board recommendation. Eight patients followed the treatment recommendation. Panobinostat was used as the backbone of therapy for the majority of patients with histone mutations with a starting dose of 16mg/m2/dose three times a week for 2 weeks followed by a 1-week break with dose escalation as tolerated. Administered doses of panobinostat ranged from 15-37mg/m2/dose with most patients tolerating a 15-24mg/m2 dose for 2–12 cycles of therapy. Several patients remain on study therapy. Additional agents recommended in combination included etoposide, cabozantinib, mebendazole, dabrafenib, trametinib, minocycline, carboplatin, metformin, dasatinib, and everolimus. Therapy has been generally well tolerated without unexpected severe toxicities. Reported grade 3 or greater treatment related toxicities include ALT elevation, mucositis, hypertension, hypertriglyceridemia, and hypokalemia and hematologic toxicities. The study has been expanded to evaluate preliminary efficacy of this approach.